Community Economic Empowerment Through the “One Pesantren One Product” Program at Pagelaran III Islamic Boarding School, Subang, Indonesia - Dandy Sobron Muhyiddin; Nurwadjah Ahmad; Andewi Suhartini; Hisam Ahyani; Naeli Mutmainah (Journal of Islamic Economics Lariba, 2022)
This study aims to uncover and explore how the implementation of the One Islamic Boarding School One Product (OPOP) Program at Pondok Pesantren Pagelarang III Subang Regency aims to create self-reliance of the people through the students. This research method uses a qualitative approach using a case study method. The data used are primary data from the research sample, namely Pondok Pesantren Pagelaran III, Subang Regency, as well as secondary data obtained from books and journal articles related to economic empowerment in Islamic boarding schools. The research technique used is data compilation, data analysis and drawing conclusions. The primary sources were obtained from the results of interviews, observations, and documentation. The study found that the concept of economic empowerment at the Pagelaran III Islamic Boarding School in Subang Regency is a concept of economic empowerment based on the Economic Development of the Ummah, which is done through the implementation of the One Islamic Boarding School One Product (OPOP) Program which is currently being intensified by the local government (Java Provincial Government). West, Indonesia). As a result, in terms of Islamic Education Theology, the One Pesantren One Product (OPOP) Program is based on the Economic Development of the Ummah.